DHARIBAH DALAM KAJIAN FILSAFAT EKONOMI ISLAM - Martua Nasution (EKSYA : Jurnal Ekonomi Syariah, 2021)
Economic philosophy is the basic orientation of economics, which can differ from one religion to another, or from one school to another because of a different frame of reference. These philosophical values ​​then become the frame of reference for Islamic economic principles. The principles of Islamic economics then become the basis for thinking and behaving in all economic activities in society, including dharibah (tax) activities. The purpose of this research is to see further how dharibah is in Islamic economic philosophy. The research method used is qualitative research with library research, namely examining written sources from various literature references, which is carried out by collecting data, then reviewing and analyzing data obtained from various written sources. The results of the study indicate that dharibah (tax) in Islam is one source of state revenue based on ijtihadulilamri approved by the House of Representatives (ahlilhalliwalaqdi) and the approval of scholars used to finance development and the benefit of the people. Some jurists are of the opinion that there is no other obligation on property other than zakat. Meanwhile, some other jurists are of the opinion that there are other obligations on assets other than zakat. These jurists do not object that the obligation on assets that is obligatory is zakat, but if conditions arise that require additional needs (darurah), then there will be additional obligations in the form of dharibah (taxes).